Effects of ventilation rate per person and per floor area on perceived air quality, sick building syndrome symptoms, and decision‐making. (17th September 2014) - Maddalena, R.; Mendell, M. J.; Eliseeva, K.; Chan, W. R.; Sullivan, D. P.; Russell, M.; Satish, U.; Fisk, W. J.
Abstract Ventilation rates (VRs) in buildings must adequately control indoor levels of pollutants; however, VRs are constrained by the energy costs. Experiments in a simulated office assessed the effects of VR per occupant on perceived air quality (PAQ), Sick Building Syndrome (SBS) symptoms, and decision‐making performance. A parallel set of experiments assessed the effects of VR per unit floor area on the same outcomes. Sixteen blinded healthy young adult subjects participated in each study. Each exposure lasted four hours and each subject experienced two conditions in a within‐subject study design. The order of presentation of test conditions, day of testing, and gender were balanced. Temperature, relative humidity, VRs, and concentrations of pollutants were monitored. Online surveys assessed PAQ and SBS symptoms and a validated computer‐based tool measured decision‐making performance. Neither changing the VR per person nor changing the VR per floor area, had consistent statistically significant effects on PAQ or SBS symptoms. However, reductions in either occupant‐based VR or floor‐area‐based VR had a significant and independent negative impact on most decision‐making measures. These results indicate that the changes in VR employed in the study influence performance of healthy young adults even when PAQ and SBS symptoms are unaffected.